Evaluation of theora and speex performance in IP videoconferencing - Ribeiro, Douglas G.; Kurashima, Celso S.; Guelfi, Adilson E.; Zuffo, Marcelo K. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
The increasing demand for applications of videoconference over IP requires not only low bandwidth but also adequate performance on networks. This paper presents the evaluation of a local network videoconferencing system based on open source codec for video and for voice signals. Specifically, these are the Theora codec and the Speex codec, which are developed under the Xiph Foundation. The satisfactory performance results we achieved indicate that both coders are potential candidates for future implementation of immersive systems.